CUSTOMER RELATIONSHIP MANAGEMENT SYSTEM: A CASE STUDY OF FLOOR MILLS IN BAHAWALPUR DISTRICT - Ghafoor Awan, Abdul; Salman Azhar, Muhammad (British Journal of Marketing Studies, 2014)
Introduction: Customer Relationship Management is the big issue in business world because the business and growth of every firms depends upon it. It is very important field that needs in-depth analysis. The author has intended to investigate it in this research paper. Objective: The objective of this research paper is to analyze the Customer Relationship Management in Flour mills of Bahawalpur and how these mills are managing their customer relations strategically. Methodology: This is an exploratory research in which deductive approach has been applied. Structured questionnaire technique has been used for data collection. Findings: The study concludes that CRM is being well strategized for the long term as it is formulated, implemented and practiced in a systematic manner. Contribution: This study can be useful in studying the customer relationship practices in other flour mills of Pakistan as this study provides basis for further research.